2019
DOI: 10.1186/s12864-019-5753-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis reveals insights into deep-sea adaptations of the dominant species, Shinkaia crosnieri (Crustacea: Decapoda: Anomura), inhabiting both hydrothermal vents and cold seeps

Abstract: Background Hydrothermal vents and cold seeps are typical deep-sea chemosynthetically-driven ecosystems that allow high abundance of specialized macro-benthos. To gather knowledge about the genetic basis of adaptation to these extreme environments, species shared between different habitats, especially for the dominant species, are of particular interest. The galatheid squat lobster, Shinkaia crosnieri Baba and Williams, 1998, is one of the few dominant species inhabiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…Although the samples we used were different from those used in Cheng et al (2019), some DEGs identified in our study showed the same expression patterns as in Cheng et al (2019), including cystathionine gamma-lyase (CSE) and heat shock protein 22 (HSP) ( Table 6), indicating they might reflect true differences between the two populations. Nevertheless, subsampling of our data clearly revealed a requirement of a larger sample size to capture the DEGs of the two populations ( Figure 6A).…”
Section: Subsampling Analyses and Comparison With Previous Studiesmentioning
confidence: 67%
See 3 more Smart Citations
“…Although the samples we used were different from those used in Cheng et al (2019), some DEGs identified in our study showed the same expression patterns as in Cheng et al (2019), including cystathionine gamma-lyase (CSE) and heat shock protein 22 (HSP) ( Table 6), indicating they might reflect true differences between the two populations. Nevertheless, subsampling of our data clearly revealed a requirement of a larger sample size to capture the DEGs of the two populations ( Figure 6A).…”
Section: Subsampling Analyses and Comparison With Previous Studiesmentioning
confidence: 67%
“…Afterward, comparison was conducted to determine an appropriate sample size for the reliable DEGs. In addition, DEGs obtained in our study were also compared with those reported in Cheng et al (2019).…”
Section: Transcriptome Assembly Completeness Assessment and Functiomentioning
confidence: 92%
See 2 more Smart Citations
“…genetic diversity, isoforms, molecular functions, and cellular functions) and quantitative (e.g. the number of genes that are differentially expressed) differences in responses to environmental pressures in a variety of organisms, including plants, insects, molluscs, crustaceans, and fish (Ye et al ., 2014; Zhao et al ., 2014; Cañas et al ., 2015; Faddeeva et al ., 2015; Cheng, Hui, & Sha, 2019; Jesus et al ., 2019). In recent years, DGE studies in social insects have highlighted a number of genes that are involved in colony organisation and adaptation to environmental constraints (Ferreira et al ., 2013; Helmkampf et al ., 2016; Lucas, Romiguier, & Keller, 2017; Willot et al ., 2018; Holman et al ., 2019).…”
Section: Discussion and Future Directionsmentioning
confidence: 99%